A Logit Regression Analysis of Homeowners in Nigeria (Global Journal of Science Frontier Research, 2013)
This paper studied the application of logit regression analysis to homeownership in Ado-Ekiti area of Ekiti State (Nigeria). The performance of the logit model in terms of classification of homeowners with respect to the average monthly income of some individuals was examined. The data of homeownership and income was fitted to the model by the WLS techniques. Result showed that the odds ratio in favour of owning a house by an individual whose average monthly income is 0.158 (N Million) was 1.0387. Also the probability of owning a house by the individual was 0.51.
Keywords: logit regression; home ownership; average monthly income; odds ratio; WLS-weighted least squares; OLS-ordinary least squares